2015
DOI: 10.1111/ans.13316
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of hyperfibrinogenemia as a predictive factor for appendiceal perforation in acute appendicitis

Abstract: Hyperfibrinogenemia was common in patients with acute appendicitis and fibrinogen may be useful as a predictive factor for appendiceal perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 10 publications
0
13
0
2
Order By: Relevance
“…Also, in a study by Noh et al [ 19 ], WBC and CRP and bilirubin levels were useful clinical markers in the diagnosis of complicated appendicitis. A study by Zhao et al [ 20 ] reported that hyperfibrinogenemia might be useful as a predictive factor for appendiceal perforation. Several studies reported that hyperbilirubinemia (>1.0 mg/dL) and CRP level (>5 mg/dL) were statistically significant markers of perforation in patients with acute appendicitis [ 21 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, in a study by Noh et al [ 19 ], WBC and CRP and bilirubin levels were useful clinical markers in the diagnosis of complicated appendicitis. A study by Zhao et al [ 20 ] reported that hyperfibrinogenemia might be useful as a predictive factor for appendiceal perforation. Several studies reported that hyperbilirubinemia (>1.0 mg/dL) and CRP level (>5 mg/dL) were statistically significant markers of perforation in patients with acute appendicitis [ 21 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies conclude that FB might be useful because of its positive correlation with the severity of the disease, being especially useful to differentiate uncomplicated from complicated appendicitis. [8][9][10][11][12][13][14] In our previous study of the diagnostic accuracy of FB in children of 5 to 14 years old, we showed that the CV to differentiate appendicitis from NSAP is 520 mg/dL. 14 In this study in preschool children, the diagnostic accuracy of FB is good to discriminate appendicitis from NSAP, with the CV in 520 mg/dL, the same figure than in older children.…”
Section: Discussionmentioning
confidence: 54%
“…White blood cell (WBC) count, absolute neutrophil count (ANC), and C-reactive protein (CRP) are the most studied and used in clinical practices. 7 Fibrinogen (FB) has been reported recently as a useful biomarker in the diagnosis of appendicitis, [8][9][10][11][12][13][14] but it has not been assessed specifically in the preschool age group. Since WBC and ANC in young children have a worst diagnostic accuracy to discriminate appendicitis than in older children, 7 it would be interesting to identify more useful inflammatory markers in this group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Tumour cells not only directly activate the coagulation cascade by producing many procoagulant proteins (tissue factor, heparanase, cancer procoagulant, and tissue factor-positive microparticles) but also stimulate the procoagulant properties of the host's haemostatic cells (endothelial cells, platelets, and leukocytes), thereby increasing plasma Fib levels [36,37]. We also cannot exclude that the pathophysiological mechanism of hypercoagulation may be secondary to the tumour-derived systemic inflammatory response and/or intra-abdominal infectious disease [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%